Uang Pelangkah in Mandailing Natal Traditional Marriage: The Perspective of 'Urf in Islamic Law - Hsb, Sakinah Azzahra (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This study discusses the practice of dowry in traditional Mandailing Natal marriages from the perspective of 'urf in Islamic law. Dowry is a tradition given to older sisters when their younger sisters marry first. This study employs a qualitative method with an empirical approach through interviews and direct observation in the village of Gunung Tua Tonga, Mandailing Natal. The findings reveal that dowry money holds social value as a form of respect and preservation of tradition. Under Islamic law, this practice can be categorized as a valid custom (‘urf shahih) as long as it does not impose undue hardship and does not become a condition for the validity of the marriage contract. However, if the practice becomes a burden and hinders marriage, it falls under the category of ‘urf fasid. Therefore, the implementation of this tradition needs to be guided so that it remains in line with the values of Sharia and does not cause harm.